Model Perhitungan Kebutuhan Pelat dan Cat Reparasi Kapal Ro-Ro KMP Titian Murni - Panut Widodo; Fahruri, M. (JURNAL BARTEK, 2026)
Material requirements estimation are very necessary before ship repairs so that work completed on time. This study aims to estimate quantity of steel plates and paint required for repair of KMP Titian Murni. Steel plate requirement estimation based on damage area, plate thickness and standard size of BKI class plate sheets, while estimate of painting requirements considering the total painting surface area, technical product specifications, and loss factor. Study method used descriptive quantitative by processing data from repair lists, shell expansion plan, and Ultrasonic Thickness Test (UTT) results. Calculation of plate requirements added with waste factor due to cutting, handling loss, and reserves. Painting requirements estimation based on Dry Film Thickness (DFT), Volume Solids (VS), loss factor, packing size, and ISO 12944. Requirement for a 6'x20' plate based on this research is 1 sheet 6 mm plate, 2 sheets 8 mm plate, 5 sheets 10 mm plate and 11 sheets 12 mm plate, total weight of 17,853 kgs. Material of PPG marine paint 680 liters Sigmacover 380, 280 liters Sigmacover 555, 580 liters Sailadvance RX, 60 liters Sigmadur 550 red, 30 liters Sigmadur 550 green, 50 liters of thinner 91-92 and 35 liters thinner 21-06, painting area of 2,265 m².